The use of reinforced concrete in the architecture of Carlo Scarpa. The Venezuelan Pavilion, the Castelvecchio Museum and the Brion Tomb - Cigarini, Tommaso (2024)
This article begins with a brief summary of the benefits of reinforced concrete in architecture. Then, it analyses the codification of the use of reinforced concrete in the Modern Movement, and then defines how, from the 1950s onwards, this material was used in a more extensive, expressive and profound way. Emblematic of this period is the architecture of Carlo Scarpa, where he used concrete extensively, taking full advantage of its possibilities and ductility, as shown in the analysis of three of his works. To finish, it can be seen how since the post-war period other architects, such as Oscar Niemeyer and Tadao Ando, have continued to use reinforced concrete in ever new and experimental ways. In current Peruvian architecture there is also a neo-brutalist trend of extreme interest, represented by recent public buildings built in Lima, which continue to use exposed reinforced concrete in a plastic and aesthetic way.